Chapter The Digital Transformation of Higher Education: From INTALL Project Results to Practical Implications for the New Normal - Tino, Concetta (Studies on Adult Learning and Education, 2023)
The Covid-19 pandemic has shaped every area of our lives in few months, and the consequent effects at personal, professional and organisational level are unprecedented. Specifically, as a consequence of this forced change, Higher Education systems have registered the necessity to transform learning and teaching processes to provide responses to new learners' needs. The aim of the paper is to present the output of a comparative group discussion of Intall project, and to show how it supports reflection on some practical implication for the New Normal. Reflecting on the output obtained through a comparative group discussion on 'Re-thinking teaching and learning during the pandemic Covid-19', the paper wants to present the main issues that the education systems have been facing during the pandemic, and to provide insight into the practical implications for the New Normal in higher and adult education. This paper provides some contributions to the debate on teaching and learning in higher education for the New Normal.